Sosialisasi Pembuatan Kerupuk Ikan Tamban Sebagai Produk Unggulan Bagi UMKM Riziq Di Desa Nenas Siam - Ritonga, Habibi Natama; Nasution, Muhammad Zaki Zikrillah Baharuddin; Anggraini, Fradilla Dewi; Zuhriah, Zuhriah (Civiliza Publishing, 2024)
Tamban fish is also one type of fish that is widely caught in the east coast area, namely coal, tamban fish includes having an affordable fish price with other fish prices. The main problems include Riziq's lack of interest and skills related to product diversification in adding economic value to tamban fish products, as well as a lack of understanding of the economic potential in Nenas Siam Village. The implementation of community service activities was carried out by providing information through lectures, discussions, and direct assistance in product diversification demonstrations. The purpose of the socialization of making tamban fish crackers is to improve skills and knowledge in developing tamban fish products, as well as increasing the economic value of tamban fish. The target of this socialization activity is the mothers of perwiritan, PKK Nenas Siam Village, and Riziq's partners. The results of this socialization activity are high quality tamban fish crackers with a spicy and savory taste. In addition, the women and PKK also gained skills in making tamban fish crackers and knowledge about the development of diversified tamban fish products in the Nenas Siam Village area.